Cefiderocol Versus Best Available Therapy in the Treatment of Critically Ill Patients with Severe Infections Due to Resistant Gram-Negative Bacteria: A Systematic Review and Meta-Analysis - Carlos Risco-Risco; César Henriquez-Camacho; Marta Herrera-Rueda; José Barberán; David Andaluz-Ojeda (MDPI AG, 2024)
Background: This study aims to assess the effectiveness and safety of cefiderocol in treating severe infections caused by multidrug-resistant Gram-negative bacteria (MDR-GNB) in critically ill patients, particularly those in intensive care units (ICUs). Methods: A meta-analysis of studies, including randomized clinical trials and observational studies in adult patients, was performed. Studies with at least 50% of critically ill patients were included. Studies with small sample size or without comparison groups were excluded. Sources included PubMed, Scopus, or Google Scholar, up to 14 August 2024. Risk of bias was assessed according to the Cochrane tool. The main outcome examined was 30-day mortality, while secondary outcomes assessed included clinical cure rates and adverse effects. Results were expressed with odds ratios. No funding was received for this study. It was registered in the International Prospective Register of Systematic Reviews (PROSPERO) with reference CRD42024563041. Results: eight studies, with 1339 patients were included in the meta-analysis. Cefiderocol treatment was associated with a lower 30-day mortality rate than other available therapies (pooled OR 0.47; 95% CI: 0.23-0.97, p = 0.04), particularly in cases of carbapenem-resistant A. baumannii infections (pooled OR 0.29; 95% CI: 0.14-0.60, p < 0.001). Although there was a non-significant trend toward higher clinical cure rates in the cefiderocol group (OR 1.59; 95% CI: 0.96-2.62, p = 0.07), the drug demonstrated at least non-inferiority when compared to other treatment options. Study limitations included moderate heterogeneity between studies, and a high risk of bias in non-RCT studies. (Five cohort studies were included). Another limitation is that five of the eight studies compared cefiderocol versus colistine, an antibiotic with known toxicity. Conclusions: The findings suggest that cefiderocol is a promising therapeutic option for managing severe MDR-GNB infections in critically ill patients, offering a potential global benefit on mortality and at least non-inferiority in the cure rate when compared with other therapies.